Temporal bone osteoblastoma involving temporomandibular joint diagnosed as simple disc disorders: A case report - Zhao, Feiya; Zhang, Xinyue; Pan, Qiaoting; Ye, Xin; Yu, Mengfei; Li, Zhiyong; Wang, Huiming (Frontiers in Surgery, 2023)
Background: Osteoblastoma is quite rare in the oromaxillo-facial region, while the mandible is always the predilection. However, in our case, the lesion was located in the left temporal articular tubercle, involving the adjacent skull base, which is extremely rare in the literature. Case reports: It had been diagnosed as the most common temporomandibular joint disorder in the local hospital before the patient came to our department, mainly due to the primary symptom, that was, the patient got pain in the left temporomandibular joint area while opening the mouth. However, we found a mass of bone lesion at the left temporal articular tubercle in MRI and CBCT, and it turned out to be an osteoblastoma after surgery. The patient's primary symptom disappeared after recovering from the surgery, and there was no indicates of complication or recurrence up to now. Conclusion: Osteoblastoma is very rare in the temporomandibular joint region. It could easily miss the possibility of a benign tumor due to its unusual location and confusing chief complaint in this case. Our report provides experience in the identification of osteoblastoma in rare sites.